DOES THE PRESENCE OF ARTERIAL HYPERTENSION INFLUENCE THE PRESCRIPTION OF ANTIPLATELET DRUGS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS?. (June 2018) - Diaconu, C.; Gaman, M.; Dobrica, E.; Cozma, M.; Dediu, G.; Gaman, A.; Arsene, A.; Dragoi, C.; Nicolae, A.; Velescu, B.; Paraschiv, B.; Tincu, R.; et al.
Abstract : Objective: Patients with type 2 diabetes mellitus (T2DM) have an increased disease burden due to the high number of comorbidities. The increased atherothrombotic risk of these patients requires the use of antiplatelet drugs, in order to prevent the occurrence of cardiovascular events. The aim of our study was to investigate the prescription patterns of antiplatelet drugs in T2DM patients, the type of antiaggregant selected and if the presence of arterial hypertension influenced the choice of medication. Design and method: We conducted a retrospective study of T2DM cases from two tertiary hospitals in Romania. Diagnostic codes of discharge diagnoses were used to identify eligible patients and to retrieve their data from medical records. Results: We included 221 T2DM patients (52.49% female, mean age 68.7 years). In total, 123 patients (55.66%) received antiplatelet drugs. Acetylsalicylic acid was selected in 93 cases (75.61%), followed by clopidogrel (39 cases, 31.71%) and ticagrelor (3 cases, 2.44%). In one case, the type of antiaggregant used could not be retrieved from the medical records. Acetylsalicylic acid was prescribed alone in 80 cases (65.04%) or in combination with either clopidogrel (10 cases, 8.13%) or ticagrelor (3 cases, 2.44%). Clopidogrel was the medication of choice in 29 cases (23.59%) without any other association of antiplatelet therapy. Ticagrelor was solely prescribed in combination with acetylsalicylic acid in our study group. Out of the patients that underwent antiplatelet therapy, 107 suffered from arterial hypertension (87.00%). In the hypertensive patients' group, acetylsalicylic acid was prescribed in 79 cases (73.83%), alone or in association with clopidogrel or ticagrelor. Acetylsalicylic acid was prescribed alone in 74 cases (69.16%), in combination with clopidogrel in 7 cases (6.54%) and in 1 case (0.93%) in association with ticagrelor. Conclusions: Our study revealed that in patients with T2DM, acetylsalicylic acid remains the most prescribed medication for the prevention and treatment of atherothrombotic events. Newer drugs, such as clopidogrel and ticagrelor, are less prescribed in Romania, mainly due to their increased cost that poses difficulty to many patients undergoing antiplatelet therapy. The presence of arterial hypertension did not influence the prescription pattern of antiplatelet drugs.